Covid-19 Outbreak and Higher Education: A Case from Taiwan - Luo, Margaret Meiling; Leon, Cesar Andres Castillo; Dampha, Makaireh; Amilcar, Rony (Archives of Business Research, 2020)
This paper aims to discuss the university transformation during the Covid-19 outbreak. We review the literature pertaining to transformation of higher education. We also provide a case study of a Taiwan university to discuss how the university takes actions to cope with the threat of Covid-19 pandemic. We expect to share a new perspective on how higher education transformation would work and describe what the future business school shall prepare for next generation learning. Lastly, we propose the post Covid-19 strategies of higher education.